1983
DOI: 10.1002/ddr.430030604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of several “new and novel” cardiotonic agents on key subcellular processes involved in the regulation of myocardial contractility: Implications for mechanism of action

Abstract: Weishaar, R.E., M. Quade, D. Boyd, J. Schenden, S. Marks, and H.R. Kaplan: The effect of several "new and novel" cardiotonic agents on key subcellular processes involved in the regulation of myocardial contractility: Implications for mechanism of action. Drug Dev. Res. 3517-534, 1983.The effect of several recently synthetized cardiotonic agents on a variety of key metabolic processes involved in regulating calcium homeostasis in the cardiac cell was evaluated in an effort to determine the mechanism of action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…Nevertheless, it is possible that they influence this Ca2" movement directly by acting upon myocardial cellular structures such as the sarcolemma or the sarcoplasmic reticulum. Weishaar et al (1983) and Hayes et al (1986) have been unable to find any convincing evidence for such an action for either sulmazole or BW A746C. Our own studies have found only weak actions for sulmazole and BW A746C upon these structures (Na+/Ca2"-exchange and Ca2l-ATPase activity at the sarcolemma; Ca2"-uptake at sarcoplasmic reticulum).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Nevertheless, it is possible that they influence this Ca2" movement directly by acting upon myocardial cellular structures such as the sarcolemma or the sarcoplasmic reticulum. Weishaar et al (1983) and Hayes et al (1986) have been unable to find any convincing evidence for such an action for either sulmazole or BW A746C. Our own studies have found only weak actions for sulmazole and BW A746C upon these structures (Na+/Ca2"-exchange and Ca2l-ATPase activity at the sarcolemma; Ca2"-uptake at sarcoplasmic reticulum).…”
Section: Discussioncontrasting
confidence: 50%
“…Most studies with sulmazole have indicated that a glycoside-like mechanism can be ruled out (Diederen & Weisenberger, 1981;From & Pierpoint, 1981;Hayes et al, 1985b), although Weishaar et al (1983) have demonstrated inhibition of myocardial Na'-K' ATPase by sulmazole at concentrations which are inotropic in vitro. In the studies presented here, inhibition of this APTase by sulmazole and BW A746C was also observed, but only at high doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbazeran is a phthalazine compound that is susceptible to AO and forms a phthalazone metabolite (Fig. 6) (Weishaar et al, 1983;Kaye et al, 1985). Whereas the phthalazone metabolite has been previously characterized using MS and tandem mass spectrometry techniques, a complete NMR characterization has not been performed.…”
Section: Downloaded Frommentioning
confidence: 99%
“…These other agents include pimobendan [54], MCI-154 [57], BM 14.578 [58], APP 201-533 [55], and DPI-201-106 [59]. Most of these agents, however, have been shown to exert other actions that could increase cardiac contractility, including inhibition of phosphodiesterase (pimobendan and sulmazole), inhibition of Na, KATPase (sulmazole), and stimulation of the sodium fast channel (DPI-201-106) [60][61][62][63]. In addition, agents that do not produce a positive inotropic response, such as bepridil and calmodizolium, have also been shown to increase calcium sensitivity [64,65].…”
Section: Calcium Sensitizersmentioning
confidence: 99%